Physicochemical properties and characterization of nata de coco from local food industries as a source of cellulose (Sifat fizikokimia dan pencirian nata de coco daripada industri makanan tempatan sebagai sumber selulosa) - Nadia Halib; Mohd. Cairul Iqbal Mohd. Amin; Ishak Ahmad (Universiti Kebangsaan Malaysia, 2012)
Nata de coco, a dessert originally from the Philippines is produced by fermentation of coconut water with a culture of Acetobacter xylinum, a gram negative bacterium. Acetobacter xylinum metabolizes glucose in coconut juice and converts it into bacterial cellulose that has unique properties including high purity, crystallinity and mechanical strength. Because the main component of nata de coco is bacterial cellulose, nata de coco was purified, extracted and characterized to determine whether pure cellulose could be isolated from it. The FTIR spectra of bacterial cellulose from nata de coco showed distinguish peaks of 3440 cm-1, 2926 cm-1, 1300 cm-1, 1440 cm-1, 1163 cm-1 and 1040 cm-1, which correspond to O-H stretching, C-H stretching, C-H bending, CH2 bending, C-O-C stretching and C-O stretching, respectively, and represent the fingerprints of pure cellulose component. Moreover, the FTIR curve showed a pattern similar to other bacterial cellulose spectra reported by report. Thermal analysis showed a DTG peak at 342°C, which falls in the range of cellulose degradation peaks (330°C - 370°C). On the other hand, the TGA curve showed 1 step of degradation, and this finding confirmed the purity of nata de coco. Bacterial cellulose powder produced from nata de coco was found to be soluble only in cupriethylenediamine, a well known solvent for cellulose; thus, it was confirmed that nata de coco is a good source of bacterial cellulose. The purity of bacterial cellulose produced from nata de coco renders it suitable for research that uses pure cellulose